Analisis Sektor-Sektor Unggulan Perekonomian Kabupaten Pulang Pisau Tahun 2010-2020 - Nurfaridah, Siti; Suherty, Lina (PPJP Universitas Lambung Mangkurat, 2023)
This study aims to determine what sectors are the leading sectors of the economy of Pulang Pisau Regency and to find out how Pulang Pisau Regency's economic performance is regarding GRDP. By knowing the top sectors in Pulang Pisau Regency, the local government can predict all available resources to improve the economy in Pulang Pisau Regency. The method used in this research is analysis; (1) LQ is used to find out the primary and non-basic sectors; (2) Shift Share is used to determine shifts and changes in the structure of the economy; (3) MRP is used to compare the amount of income in an economic sector in a small area with a larger area. This study uses secondary data on GDP based on constant prices in Pulang Pisau Regency. The combined identification results from the analysis of LQ, Shift Share, and MRP are known to be the Agriculture, Forestry and Fisheries, Construction, Accommodation, and Food and Drink Providers, Information and Communication sectors, which are the leading sectors in Pulang Pisau Regency.